The Application of Learning to Reading Without Spell Method in Increase the Reading Skill in The First Grade Elementary School Students - Kurniawati, Fitria Dwi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research have purpose to increase the reading the skill in the firsth grade elementary school students. This research is a classroom action research conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. The subjects were students first grade elementary school. Data source of this study are were students first grade elementary school, first grade elementary school teacher, and observers. The data analysis technique consists of three components, that is data reduction, data presentation, and conclusion or verification. The results show that the application of learning to reading without spell metod can be improve the reading skillÂ  first grade student elementary school.